Auditory Brainstem Response, ABR - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Auditory cortical processing in noise in younger and older adults - Mccullagh, Jennifer; Shinn, Jennifer B (Hearing, Balance and Communication, 2013)
Objective: A common clinical complaint among older adults is difficulty hearing in noise, even in those with normal or near-normal peripheral hearing sensitivity. Researchers have demonstrated behavioral hearing in noise deficits in older adults, but to date limited evidence, particularly objective, exists elucidating the effects of age on auditory cortical processing in noise. The purpose of this investigation was to explore age related differences in auditory cortical processing at multiple signal-to-noise ratios (SNRs). Study design: Twenty normal-hearing young adults and 15 normal-hearing older adults participated in the study. Late auditory evoked potential (N1 and P2) latencies and amplitudes were measured in quiet and at three signal-to-noise ratios (SNRs) (+ 20, + 10, and 0 SNR). Repeated measures analyses of variance (ANOVA) were utilized to determine if statistically significant differences existed. Results: Significant group by listening condition interactions existed for N1 and P2 amplitudes. P2 latencies were significantly longer for the older adult group compared to the younger adult group. In addition, N1 and P2 amplitudes were significantly smaller for the younger adult group compared to the older adult group. Conclusion: Results suggest a possibly greater reduction in the synchronous neuronal response from quiet to noisy conditions in older adults than in younger adults. © 2013 Informa Healthcare.
Keywords: Aging; Auditory late potentials; Hearing in noise; N1; P2; dept.cmd; peer-reviewed

Measures of binaural interaction - McCullagh, Jennifer; Bamiou, Doris (Handbook of (Central) Auditory Processing Disorders: Auditory neuroscience and diagnosis, 2013)
Keywords: dept.cmd

Brainstem Audiometry - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Cochlea - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Deafness - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Dichotic Listening - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Hearing - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Otitis Media - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Pediatric Speech Intelligibility Test - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Screening Test for Auditory Processing Disorders - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Deaf-Blind - McCullagh, Jennifer; Weiss, Deborah (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd